Using Second Life in an educational environment - Banek Zorica, Mihaela (2008)
Emerging immersive worlds have created a new space for education and training. Among the various theme based and general Multi-User Virtual Environments and Massively Multiplayer Online Role-Playing Games Second life has emerged as one of the environments mostly used in formal and life-long education.